The interaction of rheumatoid factor with hepatitis B surface antigen-antibody complexes. - Markenson, J A (1975)
A solid phase radioimmunoassay was developed in which the hepatitis B surface antigen was adsorbed to the surface of plastic beads. When the antigen-coated beads were incubated with human IgG antibody against hepatitis B surface antigen, immune complexes were formed on the solid phase surface. IgM rheumatoid factor was found to bind to the hepatitis B surface antigen-antibody complexes but not to the antigen or the IgG antibody alone. Since both hepatitis B surface antigen-antibody complexes and rheumatoid factor are commonly present in type B viral hepatitis, it is suggested that rheumatoid factor may play a role in the pathogenesis of this viral disease in man.